Effects of azilsartan medoxomil compared with olmesartan and valsartan on ambulatory and clinic blood pressure in patients with type 2 diabetes and prediabetes. Issue 4 (April 2016) - White, William B.; Cuadra, René H.; Lloyd, Eric; Bakris, George L.; Kupfer, Stuart
Abstract : Background: Angiotensin receptor blockers (ARBs) are preferred antihypertensive therapies in patients with type 2 diabetes mellitus (T2DM). Azilsartan medoxomil (AZL-M) is a potent ARB for the treatment of stages 1-2 hypertension. We compared the efficacy, safety, and metabolic effects of AZL-M to both valsartan (VAL) and olmesartan (OLM), separately in patients with impaired fasting glucose (prediabetes mellitus) and T2DM. Methods: A pooled analysis of 3821 patients from three separate randomized placebo-controlled trials comparing the effects of AZL-M (40 and 80 mg), OLM (40 mg), VAL (320 mg), and placebo on changes in ambulatory and clinic blood pressure (BP) among patients with hypertension and prediabetes mellitus or T2DM was performed. Two analysis pools were created to facilitate comparisons: Pool A included patients who received placebo, AZL-M or OLM and Pool B included those who received AZL-M or VAL. Within each pool, patients were stratified by glycemic subgroups (normoglycemic, prediabetes mellitus, or T2DM) based on hemoglobin A1c values. Changes from baseline in both 24-h and clinic SBP were the primary efficacy assessments. Results: Baseline 24-h mean SBPs were approximately 145 and 146 mmHg in the prediabetes mellitus and T2DM subgroups, respectively; corresponding clinic SBPs were approximately 158 and 159 mmHg. Baseline hemoglobin A1c values for each subgroup (both pools) were normoglycemic, 5.3%; prediabetes mellitus, 6.0%; and T2DM, 6.9%. Changes from baseline in 24-h or clinic SBP were significantly greater with AZL-M, 80 mg compared with either OLM 40 mg or VAL 320 mg in all subgroups in each pool. Safety and tolerability were similar among the active treatment and placebo subgroups. Conclusion: These analyses indicate that AZL-M, 80 mg/day lowers SBP by a greater magnitude than OLM or VAL at maximally approved doses in patients with prediabetes mellitus and T2DM. These findings have important clinical implications for this high-risk patient group. Abstract : Supplemental Digital Content is available in the text